MNSs genotyping by MALDI‐TOF MS shows high concordance with serology, allows gene copy number testing and reveals new St(a) alleles - Meyer, Stefan; Vollmert, Caren; Trost, Nadine; Sigurdardottir, Sonja; Portmann, Claudia; Gottschalk, Jochen; Ries, Judith; Markovic, Alexander; Infanti, Laura; Buser, Andreas; Amar el Dusouqui, Soraya; Rigal, Emmanuel; et al. (British journal of haematology, 2016)
Results of genotyping with true high‐throughput capability for MNSs antigens are underrepresented, probably because of technical issues, due to the high level of nucleotide sequence homology of the paralogous genes GYPA, GYPB and GYPE. Eight MNSs‐specific single nucleotide polymorphisms (SNP) were detected using matrix‐assisted laser desorption/ionization, time‐of‐flight mass spectrometry (MALDI‐TOF MS) in 5800 serologically M/N and S/s pre‐typed Swiss blood donors and 50 individuals of known or presumptive black African ethnicity. Comparison of serotype with genotype delivered concordance rates of 99·70% and 99·90% and accuracy of genotyping alone of 99·88% and 99·95%, for M/N and S/s, respectively. The area under the curve of peak signals was measured in intron 1 of the two highly homologous genes GYPB and GYPE and allowed for gene copy number variation estimates in all individuals investigated. Elevated GYPB:GYPE ratios accumulated in several carriers of two newly observed GYP*401 variants, termed type G and H, both encoding for the low incidence antigen St(a). In black Africans, reduced GYPB gene contents were proven in pre‐typed S‐s‐U‐ phenotypes and could be reproduced in unknown specimens. Quantitative gene copy number estimates represented a highly attractive supplement to conventional genotyping, solely based on MNSs SNPs.